CERTAIN TYPES OF SEPARATION AXIOMS IN TRI-TOPOLOGICALSPACES - Hameed, Najlae; Abid, Mohammed (Iraqi Journal of Science, 2024)
In this paper, we introduce and study new types of separation axioms in tritopologicalspaces, where we defined it using new types of closed set but notnecessarily closed sets. Several properties of these concepts are proved.